First confirmed record of the Guianan White-eared Opossum, Didelphis imperfecta Mondolfi & Pérez-Hernández, 1984 (Didelphimorphia, Didelphidae), from Colombia - Tania Marisol González (Check List, 2020)
We report the first confirmed occurrence of the Guianan White-eared Opposum Didelphis imperfecta Mondolfi & Pérez-Hernéndez, 1984 (Didelphimorphia: Didelphidae) from Colombia. The individual was captured in a tropical lowland rain forest in the easternmost portion of the Colombian Orinoco Llanos region. The species is endemic of the Guiana Shield and has the smallest distribution area among the species of the genus. Our record shows that the Orinoco river does not constitute a biogeographical barrier for the species. To date, only two species of the genus Didelphis Linnaeus, 1758 have been recorded in Colombia, our results increase the reported number of records for this genus.